Does Familiarity Breed Esteem? A Field Experiment on Emergent Attitudes Toward Members of Congress. (March 2023) - Esterling, Kevin M.; Minozzi, William; Neblo, Michael A.
Canonical theories of democratic representation envision legislators cultivating familiarity to enhance esteem among their constituents. Some scholars, however, argue that familiarity breeds contempt, which if true would undermine incentives for effective representation. Survey respondents who are unfamiliar with their legislator tend not to provide substantive answers to attitude questions, and so we are missing key evidence necessary to adjudicate this important debate. We solve this problem with a randomized field experiment that gave some constituents an opportunity to gain familiarity with their Member of Congress through an online Deliberative Town Hall. Relative to controls, respondents who interacted with their member reported higher esteem as a result of enhanced familiarity, a mediation effect supporting canonical theories of representation. This effect is statistically significant among constituents who are the same political party as the member but not among those of the opposite party, although in neither case did familiarity breed contempt.